Cataract surgical coverage rate among adults aged 40 years and older - Tana, Lusianawaty (Universa Medicina, 2009)
Cataract is a leading cause of curable blindness. Hence, in its global declaration of âVision 2020 Right to Sightâ, the World Health Organization (WHO) encouraged its member countries to address the problem of incident cataract. Many factors are related to the cataract surgical coverage rate, such as gender and diabetes mellitus. The objective of this study was to determine the cataract surgical coverage rate and investigate the determinants factors of cataract surgical coverage rate among adults 40 years old and above with cataract. A cross sectional study was conducted using National Basic Health Research (Riskesdas) 2007 data. Cataract surgery was defined as surgery conducted within the last 12 months before the survey was performed. There were 6939 subjects (3105 male, 3834 female) who fulfilled the study criteria. The cataract surgical coverage rate was 19.3%. The cataract surgical coverage rate was lower in subjects with low education, in the group of farmers/fishermen/laborers, in the 40-49 years age group, in rural areas, and in subjects of low socioeconomic status (p<0.05). The cataract surgical coverage rate was not different between gender and diabetes mellitus (p>0.05). Determinants that were related to cataract surgical coverage rate were age, type of area of residence, socioeconomic status, and region of residence (p<0.001). The implementation of educational programs and reforms to local ophthalmic health services may improve the cataract surgical coverage rate.